PELATIHAN LARI INTERVAL 4 X 50 METER DI PANTAI BERPASIR LEBIH MENINGKATKAN KECEPATAN LARI 100 METER DARIPADA PELATIHAN LARI INTERVAL 4 X 50 METER DI LAPANGAN PADA SISWA KELAS XSMK N KAKULUK MESAK NTT. - Nahak, Benediktus; Pangkahila, Alex; Purnawati, Susy (Sport and Fitness Journal; Volume 2, No.2, 2014, 2014)
The speed is one of the biomotoriccomponents which dominantin the run race100 meters. 100 meters run is part of athletics which has a short duration, highintensity and anaerobic systems develop. The purpose of this study was todetermine the increasing of 100 meter run speed, therefore this research is anexperimental study was conducted in SMK N Kakulukmesak Belu regency NTT,for 6 months from March - May 2014, with the frequency of exercise 3 times aweek. This study uses two types of training, and were divided into two treatmentgroups, ie group one is the training of interval run 4 x 50 meter on the sandybeach 4 reps 3 sets andgroup twois the interval run 4 x 50 meter in the yard 4 reps3 sets, implemented in the afternoon at 15.30 to 17.00 pm in the yard of SMK NKakulukmesak and Atapupu Beach, Belu regency - NTT. Sample was 20 people,chosen simple randomly from a population of 53 people who meet therequirements of inclusion and exclusion. The number of samples for each group is10 people. The speed of 100 meter run was measured using stopwatch, while the100-meter dash speed data before and after training in both groups, were testedwith parametric statistical analysis. With a paired t-test of mean difference testsobtained the 100 meter dash speed after training on each group with p <0.05. Themean speed of 100 meters before training in the group one is 16.06 seconds and13.01 seconds after training. Means increased speed of 3:05 seconds, or at =19:02%. While the average running speed of 100 meters in group two beforetraining is 16.02 seconds and after training is 13.95 seconds, the increasing ofspeed is 12.91%. This shows that the average speed of 100 meters before and aftertraining on each group there is a significant difference, with value p<0.05. Thusthe training of group 1is interval run 4 x 50 meter on the sandy beach and intervaltraining run 4 x 50 meters in the yard, after training is equal to increase the speedof the 100 meterin 10th grade student of SMK N Kakulukmesak. However, in theanalysis of data on the paired sample test, the speed training of group oneon thesandy beach is faster = 0.94 seconds than thetraining of group twoin the yard.
Keywords: Training, Speed,Interval Running